CBX2 and EZH2 cooperatively promote the growth and metastasis of lung adenocarcinoma - Fei-Fei Hu; Hao Chen; Yang Duan; Bei Lan; Chun-Jie Liu; Hui Hu; Xu Dong; Qiong Zhang; Yi-Ming Cheng; Min Liu; An-Yuan Guo; Chenghao Xuan (Elsevier, 2022)
The disruption of epigenetic regulation is common in tumors; the abnormal expression of epigenetic factors leads to cancer occurrence and development. In this study, to investigate the potential function of histone methylation regulators in lung adenocarcinoma (LUAD), we performed differential expression analysis using RNA-seq data downloaded from The Cancer Genome Atlas (TCGA) database, and identified CBX2 and EZH2 as obviously upregulated histone methylation regulators. CBX2 knockdown significantly inhibited LUAD cell growth and metastasis in vitro and in vivo. The combined high expression of CBX2 and EZH2 was an indicator of poor prognosis in LUAD. The inhibition of both CBX2 and EZH2 exerted cooperative suppressive effects on the growth and metastasis of LUAD cells. Mechanistically, we revealed that CBX2 and EZH2 downregulated several PPAR signaling pathway genes and tumor suppressor genes through binding to their promoter cooperatively or separately. Furthermore, knockdown of CBX2 improved the therapeutic efficiency of EZH2 inhibitor on A549 cells. Our study reveals the cooperative oncogenic role of CBX2 and EZH2 in promoting LUAD progression, thereby providing potential targets for LUAD diagnosis and therapy.